Pemanfaatan Sumber Daya Lingkungan sebagai Bagian dari Implementasi Teknologi Green Manufacturing - Masayu Rosyidah; Masayu Azizah; Lilik Pranata (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Producing environmentally friendly products, efficient and sustainable use of natural resources, and reducing negative impacts on the environment are the goals of the green production approach. So there is a need for education for young people to protect the environment with us. The purpose of this PkM activity is to introduce students to the Utilization of Environmental Resources as Part of the Implementation of Green Manufacturing Technology. The method of activity carried out by means of education and assistance in managing a green environment. The education participants were students of Madrasah Ibtidaiyah and SMP Yayasan Ummul Quro Al-Hamidiyah totaling 50 students. The activity was carried out on Thursday, December 19, 2024. The results of the activity showed that students were very enthusiastic about participating, and students had understood what was explained by the speaker. The conclusion of the activity showed that there was an increase in student knowledge after being given education about Environmental Resources as Part of the Implementation of Green Manufacturing Technology.